The relationship between clinical nurses’ feelings of underqualification and work withdrawal behavior: the multiple mediating roles of self-disgust and self-efficacy - Yang, Ran; Li, Na; Fan, Yuxia; Yuan, Zhenhao; Lin, Cuixia; Shen, Yan; Yang, Linlin (Frontiers in Psychology, 2025)
PurposeThe purpose of this study is to analyze the influence of three variables—feelings of underqualification, self-disgust, and self-efficacy—on work withdrawal behavior, with the aim of drawing attention to the mental health of nurses.MethodsA total of 300 nurses were recruited in Shandong Province, China for the survey. Participants completed the General Information Questionnaire, the Perceived Inadequate Qualifications Scale, the Work Withdrawal Behavior Scale, the Self-Disgust Scale, and the General Self-Efficacy Scale. The potential relationships between these variables were explored.ResultsThe work withdrawal behavior of nurses in this study is characterized as being at a lower middle level. Work withdrawal behavior was positively correlated with feelings of underqualification and self-disgust, while showing a negative correlation with self-efficacy. Self-disgust and self-efficacy indirectly influence perceived underqualification and work withdrawal behavior. Both the mediating effect and the chain mediating effect were found to be significant.ConclusionSelf-disgust and feelings of underqualification can aggravate the work withdrawal behavior of nurses, while improving self-efficacy can help reduce this behavior. Nursing managers should create opportunities for skill development, prioritize the physical and mental health of nurses, and take steps to minimize work withdrawal behavior, thereby improving the quality of clinical nursing.